Outbreak of cephalosporin resistant Enterobacter cloacae infection in a neonatal intensive care unit. Issue 2 (February 1987) - Modi, N; Damjanovic, V; Cooke, R W
Abstract : Enterobacter cloacae resistant to third generation cephalosporins emerged rapidly during an outbreak of serious infections due to this organism in a neonatal intensive care unit where ampicillin and gentamicin were used as first line antibiotic treatment. Organisms resistant to cephalosporins were isolated from 12 infants, six of whom developed systemic infection. Two infants died. Isolates of E. cloacae from four of five infants treated with cefotaxime showed a loss of sensitivity to this antibiotic during treatment, but in the three infants who survived sensitive organisms were again isolated after treatment had stopped. Stopping treatment with the cephalosporins, closure of the unit to new admissions, and strict cohorting of colonised infants resulted in a prompt end to the outbreak. This outbreak suggests that the routine use of third generation cephalosporins for suspected sepsis may be inappropriate in the presence of a large reservoir of organisms with the potential for rapidly developing resistance. Routine bacteriological surveillance, however, might permit their use on a rotational basis.